Realistic Ab Initio Predictions of Excimer Behavior under Collective Light-Matter Strong Coupling - Matteo Castagnola; Marcus T. Lexander; Henrik Koch (Physical Review X)
Experiments show that light-matter strong coupling affects chemical properties, though the underlying mechanism remains unclear. A major challenge is to perform reliable and affordable simulation of molecular behavior when many molecules are collectively coupled to the same optical mode. This paper presents an ab initio quantum electrodynamics coupled cluster method for the collective strong coupling regime. The model describes electronic and electron-photon correlation within a molecular subsystem, while a simplified description of the collective polaritonic excitations allows for a realistic microscopic light-matter coupling. The developed framework provides a computationally tractable route to accurately simulate a molecule in a collective environment, which is unfeasible when several molecules are treated explicitly. We investigate the properties of the argon dimer under strong light-matter coupling. In the single-molecule regime (large light-matter coupling), the potential energies are substantially modified, weakening the excimer bond. In contrast, in the collective regime (small light-matter coupling, large number of molecules), the ground state potential energy surface and the first vibrational levels of the excited state do not change significantly. However, collective strong coupling produces an abrupt transition in the vibrational landscape of the excimer, causing higher vibrational levels to behave similarly to the vibrations in the ground state. We expect the excimer formation to be inhibited by light-matter strong coupling and conclude that chemical properties are altered via distinct mechanisms in the collective and single-molecule regimes. We also discuss fundamental aspects of polaritonic chemistry, such as resonance conditions and sudden changes of the molecular properties when a critical collective coupling strength is achieved.